The quest for a liberal-socialist democracy and development : against the behemoth - Katunarić, Vjeran (Cambridge Scholars Publishing, 2018)
This book explains why elective affinity exists between democratic and non-democratic ideologies and why liberal socialism as a compromise between liberalism and socialism did not succeed in the 20th century. As is shown here, the main reason for such affinity is the self-incurred immaturity of both ideologies. Although both concepts diverged from the beginning, as contenders in the political scene, they gradually became more antagonistic and self-contained. Furthermore, the idea of the self-production of both liberalism and socialism system absorbed their democratic potential and expanded the elective affinity toward authoritarian ideologies and regimes. The book also provides a set of policies of liberal socialism that may serve to remove the liabilities of liberalism and socialism as separate ideologies and policies and produce conditions for democratic and economically sustainable development--back cover.